Ochrona prawna grobów wojennych – uwagi de lege lata postulaty de lege ferenda - Trzciński, Maciej (Lʹvìvsʹkij nacìonalʹnij unìversitet ìmenì Ìvana Franka, 2021)
Protection of war graves is the task of the state. After the liquidation in 2016 of the Council for the Remembrance of Combat and Martyrdom which performed the majority of duties in this area, the competences of this institution were assigned primarily to the Ministry of Culture and National Heritage and partly to the Institute of National Remembrance. The issue of protection of graves is not only the issue of diffused competences of various administrative bodies and institutions, but also the issue of research on previously unrecognized graves and war cemeteries, including their recording. There search conducted on this subject reveals not only shortcomings of legal nature but also real threats among which there is deliberate destruction and robbing of war graves.
Keywords: war graves; protection; legal protection system; practical activities; voênnì pohovannâ; zahist; sistema pravovogo zahistu; praktičnì zahodi